Core-shell type composite photocatalyst SnIn4S8 / COF as well as preparation method and application thereof

By growing sheet-like SnIn4S8 on the surface of the spherical covalent organic frame material PT-COF, forming the core-shell composite photocatalyst SnIn4S8/COF, the problem that existing photocatalysts are difficult to efficiently photocatalyze the generation of hydrogen peroxide in pure water and air, and achieving efficient and low-cost hydrogen peroxide production.

CN119500262APending Publication Date: 2025-02-25HUBEI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422430.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing photocatalysts are difficult to efficiently photocatalyze the production of hydrogen peroxide in pure water and air systems, and the production cost is high, making it difficult to separate later.

Method used

The core-shell composite photocatalyst SnIn4S8/COF is used, which forms a core-shell structure by growing sheet-shaped SnIn4S8 on the surface of the spherical covalent organic frame material PT-COF, simplifying the synthesis process and improving controllability.

Benefits of technology

It realizes efficient photocatalytic production of hydrogen peroxide in pure water and air, reduces production costs, simplifies the separation and collection of hydrogen peroxide, and has good economic value and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500262A_ABST
    Figure CN119500262A_ABST
Patent Text Reader

Abstract

The invention provides a core-shell type composite photocatalyst SnIn4S8 / COF as well as a preparation method and application of the core-shell type composite photocatalyst SnIn4S8 / COF. The SnIn4S8 / COF is of a core-shell structure formed by covering flaky SnIn4S8 on the surface of spherical PT-COF, and the preparation method of the SnIn4S8 / COF comprises the following steps: in an organic solvent, performing a reaction on 2, 3-dihydroxy terephthalaldehyde and 1, 3, 4-trihydroxy terephthalaldehyde to form a core-shell structure; the preparation method comprises the following steps: synthesizing a Schiff base covalent organic framework material, namely PT-COF, by taking 2, 3, 5-tri (4-aminophenyl) benzene as a reaction monomer, and growing SnIn4S8 on the surface of the PT-COF in situ by a wet chemical method to obtain the core-shell type composite photocatalyst SnIn4S8 / COF. The preparation method is simple in synthesis process, simple and convenient to operate, high in controllability, mild in reaction condition and high in yield; the SnIn4S8 / COF can generate hydrogen peroxide through efficient photocatalysis in an open system of pure water and air atmosphere, more reaction active sites can be provided, the transmission path of photo-generated electrons can be shortened, the recombination rate of photo-generated electron-hole pairs can be reduced, and the separation efficiency of the photo-generated electron-hole pairs can be improved, so that the photocatalytic activity can be remarkably improved, and the photocatalytic activity can be improved. And later separation and collection of hydrogen peroxide are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of photocatalysis, and specifically relates to a core-shell composite photocatalyst SnIn4S8 / COF for photocatalytic production of hydrogen peroxide in a pure water and air system, and a preparation method and use thereof. [Background technology]

[0002] Hydrogen peroxide (H2O2) is a green and environmentally friendly oxidant widely used in disinfection, bleaching, wastewater treatment and chemical synthesis. At present, the industrial production of hydrogen peroxide mainly adopts the anthraquinone process, which produces more than 95% of the world's total hydrogen peroxide production each year. Therefore, it is urgent to develop a low-cost, green and sustainable H2O2 production technology.

[0003] Semiconductor photocatalytic production of H2O2 technology is an environmentally friendly, safe and energy-saving technology. It uses abundant oxygen and water on the earth as raw materials and solar energy as energy. It has the advantages of mild reaction conditions, safety, and zero carbon emissions. It shows great potential to replace the traditional anthraquinone process and is considered to be an ideal technology for producing H2O2. The preparation of high-performance and stable photocatalysts is the key to this technology. It has been reported that a variety of materials such as ZnO, CdS, C3N4, metal organic frameworks (MOFs) and covalent organic frameworks (COFs) can be used for photocatalytic production of H2O2. Among them, COF, as a crystalline porous covalent organic polymer, is one of the ideal candidate materials for photocatalytic production of H2O2 due to its large specific surface area, adjustable structure, high thermal stability and chemical stability. However, a single COF as a photocatalyst has problems such as high recombination rate of photogenerated electrons and holes, which seriously limits its application. In addition, most of the existing photocatalysts rely on hole sacrificial agents such as ethanol and benzyl alcohol, and need to introduce pure oxygen into the reaction system, which will increase the production cost of hydrogen peroxide and increase the difficulty of hydrogen peroxide separation in the later stage. The development of COF-based photocatalysts that can photocatalytically synthesize H2O2 in pure water and air systems is undoubtedly of greater practical significance. [Summary of the invention]

[0004] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and meet the needs of research and application in this field, and to provide a core-shell composite photocatalyst SnIn4S8 / COF, which has a simple synthesis process, simple operation, strong controllability, mild reaction conditions, high yield, and no need for sacrificial agents, and can efficiently photocatalytically produce hydrogen peroxide in air and pure water, as well as a preparation method and use thereof.

[0005] To achieve the above objectives, the present invention first provides a core-shell composite photocatalyst SnIn4S8 / COF, which is a core-shell structure formed by flaky SnIn4S8 covering the surface of spherical PT-COF.

[0006] The present invention also provides a method for preparing the core-shell composite photocatalyst SnIn4S8 / COF, which is characterized by comprising the following steps:

[0007] 1) In an organic solvent, a Schiff base covalent organic framework material, PT-COF, was synthesized using 2,3-dihydroxyterephthalaldehyde and 1,3,5-tri(4-aminophenyl)benzene as reaction monomers;

[0008] 2) In situ growth of SnIn4S8 on the surface of the PT-COF is carried out by a wet chemical method to obtain the core-shell composite photocatalyst SnIn4S8 / COF.

[0009] Preferably, the method for preparing the core-shell composite photocatalyst SnIn4S8 / COF is characterized by:

[0010] Step 1) is to add 2,3-dihydroxyterephthalaldehyde and 1,3,5-tri(4-aminophenyl)benzene to acetonitrile, then add acetic acid solution, stir, stand for reaction, centrifuge the reaction solution, wash the obtained solid with N,N-dimethylformamide, tetrahydrofuran and ethanol in sequence, and dry to obtain PT-COF;

[0011] Step 2) is to disperse the PT-COF prepared in step 1) into anhydrous ethanol, then add SnCl4·5H2O, InCl3·4H2O and thioacetamide, stir, and heat to react. The reaction solution is centrifuged, and the obtained solid is washed with water and ethanol in turn, and dried to obtain the core-shell composite photocatalyst SnIn4S8 / COF.

[0012] Further preferably, the method for preparing the core-shell composite photocatalyst SnIn4S8 / COF is characterized by:

[0013] In step 1), the molar ratio of 2,3-dihydroxyterephthalaldehyde to 1,3,5-tri(4-aminophenyl)benzene is 1:1 to 2:1, and the acetic acid solution is 3 to 12 mol.L -1 ; The stirring is stirring at room temperature for 1 to 10 minutes; the standing reaction is standing at room temperature for 3 days; the washing is washing with N,N-dimethylformamide, tetrahydrofuran and ethanol 1 to 3 times each; the drying is drying at 40-80°C for 12 to 48 hours;

[0014] In step 2), the dispersion is ultrasonic dispersion; the molar ratio of the added substances is SnCl4·5H2O:InCl3·4H2O:thioacetamide=1:4:8~1:4:16; the stirring is stirring at room temperature for 30~60min; the heating reaction is heating to 60~80℃ for 2~4h; the washing is washing with water and ethanol respectively 1~3 times in sequence; the drying is drying at 40-60℃ for 12~48 hours.

[0015] The present invention further provides the use of the core-shell composite photocatalyst SnIn4S8 / COF in the preparation of hydrogen peroxide, wherein the use is that the core-shell composite photocatalyst SnIn4S8 / COF is used as a catalyst in the photocatalytic generation of hydrogen peroxide.

[0016] Preferably, the light source used in the photocatalytic reaction of generating hydrogen peroxide is a 300W xenon lamp with a 420nm cut-off filter.

[0017] The beneficial effects of the present invention include:

[0018] ① The flaky SnIn4S8 was in-situ grown on the surface of the spherical COF to construct the core-shell composite photocatalyst SnIn4S8 / COF. The tight coating of the flaky SnIn4S8 on the spherical COF not only provides more reactive sites, but also helps to shorten the transmission path of photogenerated electrons, reduce the recombination rate of photogenerated electron-hole pairs, and improve the separation efficiency of photogenerated electron-hole pairs, thereby significantly improving the photocatalytic activity;

[0019] ② The synthesis process of the present invention is simple, easy to operate, highly controllable, mild in reaction conditions and high in yield;

[0020] ③ The core-shell composite photocatalyst SnIn4S8 / COF prepared in the present invention can efficiently photocatalytically produce hydrogen peroxide in an open system of pure water and air atmosphere, has low production cost, is conducive to the later separation and collection of hydrogen peroxide, and has good economic value and application prospects.

Brief Description of the Drawings

[0021] Figure 1 The scanning electron microscope images and transmission electron microscope images in Example 1, wherein (a) is a scanning electron microscope image of SnIn4S8, (b) is a scanning electron microscope image of PT-COF, (c) is a scanning electron microscope image of the SnIn4S8 / COF composite, and (d) is a transmission electron microscope image of the SnIn4S8 / COF composite;

[0022] Figure 2 X-ray powder diffraction patterns of SnIn4S8, PT-COF and SnIn4S8 / COF composite in Example 1;

[0023] Figure 3The rate diagram of photocatalytic production of hydrogen peroxide by SnIn4S8, PT-COF and SnIn4S8 / COF composite under visible light irradiation in Example 1;

[0024] Figure 4 The photocurrent diagrams of SnIn4S8, PT-COF and composite SP-20 in Example 1;

[0025] Figure 5 The impedance diagrams of SnIn4S8, PT-COF and composite SP-20 in Example 1;

[0026] Figure 6 is the electron paramagnetic resonance spectrum of the composite SP-20 in Example 1;

[0027] Figure 7 This is a graph showing the rate of photocatalytic production of hydrogen peroxide by the composite SP-20 in Example 1 under different conditions. [Specific implementation method]

[0028] The technical scheme of the present invention is now described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit and essence of the present invention, the modifications or replacements made to the steps or conditions of the present invention all belong to the scope of the present invention.

[0029] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0030] Example 1 Preparation of core-shell composite photocatalyst SnIn4S8 / COF

[0031] 1) Add 125 mg (0.75 mmol) of 2,3-dihydroxyterephthalaldehyde (PDA) and 176 mg (0.5 mmol) of 1,3,5-tris(4-aminophenyl)benzene (TAPB) to a round-bottom flask containing 50 mL of acetonitrile, and then add 5 mL of 12 mol.L -1 acetic acid solution, stirred at room temperature for 2 minutes, and then allowed to stand at room temperature for 3 days. After the reaction was completed, the reaction solution was centrifuged, and the obtained solid was washed with N, N-dimethylformamide, tetrahydrofuran and ethanol three times respectively. Finally, the product was placed in an electric blast drying oven and dried at 60°C for 48 hours to obtain a spherical covalent organic framework material PT-COF with a yield of 92%;

[0032] 2) 20 mg PT-COF was ultrasonically dispersed in 60 mL of anhydrous ethanol, and then 34 mg (0.096 mmol) SnCl4·5H2O, 112 mg (0.384 mmol) InCl3·4H2O and 86 mg (1.152 mmol) thioacetamide were added in sequence. After stirring at room temperature for 30 min, the mixture was heated to 70°C for reaction for 3 h. After the reaction was completed, the reaction solution was centrifuged, and the obtained solid was washed with water and ethanol three times respectively. Finally, the product was dried at 60°C for 48 hours to obtain a core-shell composite photocatalyst SnIn4S8 / COF (denoted as SP-20, which indicates that the mass of PT-COF accounts for 20% of the theoretical total mass of the composite SnIn4S8 / COF), with a yield of 90%. Other composite samples SP-10 and SP-30 were synthesized in a similar manner. In the above preparation process, if PT-COF is not added, a pure SnIn4S8 sample is obtained.

[0033] Example 2 Preparation of core-shell composite photocatalyst SnIn4S8 / COF

[0034] The amount of acetic acid solution used in step 1) is 10mL 6mol.L -1 , the stirring time at room temperature was 1 min, and the remaining steps were repeated in Example 1, and the yield of the obtained spherical covalent organic framework material PT-COF was 91%;

[0035] Step 2) The amounts of SnCl4·5H2O, InCl3·4H2O and thioacetamide added were 75 mg (0.22 mmol), 253 mg (0.88 mmol) and 194 mg (2.64 mmol), respectively. The stirring time at room temperature was 60 min, and then the mixture was heated to 80°C for 4 h. The remaining steps were repeated in Example 1. The yield of the core-shell composite photocatalyst SnIn4S8 / COF was 92%.

[0036] Example 3 Preparation of core-shell composite photocatalyst SnIn4S8 / COF

[0037] The amount of acetic acid solution used in step 1) is 6mL 9mol.L -1 , the stirring time at room temperature was 2 min, and the remaining steps were repeated in Example 1, and the yield of the obtained spherical covalent organic framework material PT-COF was 89%;

[0038] Step 2) The amounts of SnCl4·5H2O, InCl3·4H2O and thioacetamide added were 20 mg (0.056 mmol), 66 mg (0.224 mmol) and 67 mg (0.896 mmol), respectively. The stirring time at room temperature was 45 min, and then the mixture was heated to 75°C for 3 h. The remaining steps were repeated in Example 1. The yield of the core-shell composite photocatalyst SnIn4S8 / COF was 90%.

[0039] Example 4 Preparation of core-shell composite photocatalyst SnIn4S8 / COF

[0040] In step 1), 125 mg (0.75 mmol) of 2,3-dihydroxyterephthalaldehyde (PDA) and 264 mg (0.75 mmol) of 1,3,5-tris(4-aminophenyl)benzene (TAPB) were added, and the concentration of the acetic acid solution was 3 mol.L -1 , stirring time at room temperature is 1 min, washing times are 1 time with N,N-dimethylformamide, 1 time with tetrahydrofuran and 1 time with ethanol, and finally the product is dried in an electric heating blast drying oven at 40°C for 48 hours, and the remaining steps are repeated in Example 1. A spherical covalent organic framework material PT-COF 88% is obtained;

[0041] Step 2) The amounts of SnCl4·5H2O, InCl3·4H2O and thioacetamide added were 75 mg (0.22 mmol), 253 mg (0.88 mmol) and 129.3 mg (1.76 mmol), respectively. After stirring at room temperature for 30 min, the mixture was heated to 60°C for 2 h. The mixture was washed with water and ethanol once each. Finally, the product was dried at 40°C for 48 hours. The remaining steps were repeated in Example 1. The yield of the core-shell composite photocatalyst SnIn4S8 / COF was 92%.

[0042] Example 5 Preparation of core-shell composite photocatalyst SnIn4S8 / COF

[0043] In step 1), 125 mg (0.75 mmol) of 2,3-dihydroxyterephthalaldehyde (PDA) and 132 mg (0.375 mmol) of 1,3,5-tris(4-aminophenyl)benzene (TAPB) were added, and the concentration of the acetic acid solution was 12 mol.L -1 , stirring time at room temperature is 10 min, washing times are 3 times with N,N-dimethylformamide, tetrahydrofuran and ethanol respectively, and finally the product is dried in an electric heating blast drying oven at 80°C for 12 hours, and the remaining steps are repeated in Example 1. The yield of the spherical covalent organic framework material PT-COF is 90%.

[0044] Step 2) The stirring time at room temperature was 60 min, and the mixture was heated to 80°C for 4 h. The mixture was washed with water and ethanol for 3 times respectively, and finally the product was dried at 60°C for 12 hours. The remaining steps were repeated in Example 1. The yield of the core-shell composite photocatalyst SnIn4S8 / COF was 91%.

[0045] Example 6 Photocatalytic production of hydrogen peroxide by core-shell composite photocatalyst SnIn4S8 / COF in pure water and air

[0046] Take 10 mg of the core-shell composite photocatalyst SnIn4S8 / COF in Example 1 and ultrasonically disperse it in 50 mL of pure water, then pour it into a photocatalytic reactor (Beijing Magnesium Ruichen Technology Co., Ltd., model MC-GF30), first stir it in the air for 30 minutes, then use a 300W xenon lamp containing a 420nm cutoff filter as a light source to irradiate the reactor, and control the temperature of the reaction system at 20°C through a cooling water circulation machine (Beijing Changliu Scientific Instrument Co., Ltd., model LX-3000), and collect samples at different time intervals (0min, 15min, 30min, 45min, 60min). The concentration of the generated hydrogen peroxide was determined by iodine titration.

[0047] Example 7 Rate of photocatalytic production of hydrogen peroxide by core-shell composite photocatalyst SP-20 under different conditions

[0048] Weigh 10 mg of the core-shell composite photocatalyst SP-20 prepared in Example 1 and put it into a beaker containing 50 mL of deionized water. After ultrasonic dispersion, pour it into a photocatalytic reactor and perform the following treatments: a) add silver nitrate (10 mg) and stir it in the air for 30 minutes; b) add p-benzoquinone (10 mg) and stir it in the air for 30 minutes; c) add ethanol (5 mL) and stir it in the air for 30 minutes; d) introduce oxygen (200 mL / min) and stir it in an oxygen atmosphere for 30 minutes; e) introduce nitrogen (200 mL / min) and stir it in a nitrogen atmosphere for 30 minutes. The temperature of the reaction system was controlled at 20°C by a cooling water circulation machine, and then a 300W xenon lamp containing a 420nm cutoff filter was used as a light source to irradiate the reactor, and the above five solutions were irradiated for 1 hour. Finally, samples under different conditions were collected, and the concentration of the generated hydrogen peroxide was determined by iodine titration.

[0049] Material characterization and performance testing:

[0050] ① The scanning electron microscopy images of SnIn4S8, PT-COF and SnIn4S8 / COF composites are shown in Figure 1 (a), (b) and (c) show the transmission electron microscopy images of SnIn4S8 / COF composites. Figure 1 (d) is shown. Figure 1 It can be seen that SnIn4S8 has a flaky amorphous structure, while PT-COF presents a spherical morphology with a rough surface and uniform particle size. When SnIn4S8 and COF are compounded, the surface of the SnIn4S8 / COF composite becomes rougher, but the spherical morphology of PT-COF is still maintained, and it can be observed that the flaky SnIn4S8 covers the spherical PT-COF surface, thus forming a core-shell structure.

[0051] ② X-ray powder diffraction (XRD) was performed on SnIn4S8, PT-COF and SnIn4S8 / COF composites (SP-10, SP-20 and SP-30). The XRD patterns obtained are as follows: Figure 2 As shown. Figure 1 It can be seen that PT-COF has good crystallinity, and the (100) and (001) crystal planes correspond to 2.56° and 25.21° respectively. The crystallinity of SnIn4S8 synthesized by wet chemical method is poor, and the (222) and (531) crystal planes correspond to 28.42° and 50.05° respectively. When SnIn4S8 is compounded with COF, due to the poor crystallinity of SnIn4S8, the strong diffraction peak intensity and high content of PT-COF mask the diffraction peak of SnIn4S8, which makes the XRD pattern of the composite basically the same as PT-COF, but as the content of SnIn4S8 in the composite increases, its crystallinity strength gradually weakens.

[0052] ②In the atmosphere of pure water and air, the photocatalytic hydrogen peroxide performance of SnIn4S8, PT-COF and SnIn4S8 / COF composites (SP-10, SP-20 and SP-30) was tested. The rates of their hydrogen peroxide production were as follows: Figure 3 As shown. Figure 3 It can be seen that the composite SP-20 has the highest photocatalytic performance in producing hydrogen peroxide. Its rate of producing hydrogen peroxide is 1.94 mol / g / h, which is 12.5 and 4.1 times that of pure SnIn4S8 and PT-COF, respectively. This shows that the catalyst has certain practical value and application prospects.

[0053] ④ Photocurrent test of SnIn4S8, PT-COF and composite SP-20, such as Figure 4 As shown. Figure 4 It can be seen that the composite SP-20 has the largest photocurrent, which indicates that after SnIn4S8 and PT-COF are combined, the core-shell composite photocatalyst SnIn4S8 / COF formed has higher light absorption and photogenerated carrier separation efficiency, thereby enhancing the photocatalytic performance of the composite.

[0054] ⑤The impedance of SnIn4S8, PT-COF and composite SP-20 was tested. Figure 5 As shown. Figure 5 It can be seen that the composite SP-20 has the smallest impedance, which indicates that after SnIn4S8 and PT-COF are combined, the core-shell composite photocatalyst SnIn4S8 / COF formed has the lowest resistance for charge transfer during photocatalysis, thereby improving the efficiency of photogenerated carrier separation, which enhances the photocatalytic performance of the composite.

[0055] ⑥ Electron paramagnetic resonance test was performed on the composite SP-20. Figure 6 As shown. Figure 6 It can be seen that the composite SP-20 cannot produce free radicals in the dark state, but after illumination, it can produce a strong superoxide free radical signal, which indicates that the photocatalytic production of hydrogen peroxide by the composite SP-20 undergoes a continuous two-electron oxygen reduction process.

[0056] ⑦ The rate of photocatalytic production of hydrogen peroxide by composite SP-20 was tested under different conditions, such as Figure 7 As shown. Figure 7 It can be seen that after adding electron sacrificial agent (silver nitrate) and superoxide free radical sacrificial agent (p-benzoquinone) to the composite SP-20, the rate of photocatalytic production of hydrogen peroxide dropped sharply, while the rate of photocatalytic production of hydrogen peroxide increased after adding hole sacrificial agent (ethanol), which shows that electrons and superoxide free radicals are key species for the production of hydrogen peroxide. In addition, compared with the air atmosphere, the rate of hydrogen peroxide production in the oxygen atmosphere increased, while the rate of hydrogen peroxide production in the nitrogen atmosphere decreased sharply, which shows that oxygen is also an important species for the photocatalytic production of hydrogen peroxide.

[0057] The specific embodiments described above are examples with better effects, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, equivalent substitutions, arrangements and combinations made without departing from the essence and principles of the present invention should be equivalent replacement methods and should be included in the protection scope of the present invention.

Claims

1. A core-shell composite photocatalyst SnIn4S8 / COF, which is a core-shell structure formed by flaky SnIn4S8 covering the surface of spherical PT-COF.

2. A method for preparing the core-shell composite photocatalyst SnIn4S8 / COF as claimed in claim 1, characterized in that The following steps are involved: 1) In an organic solvent, a Schiff base covalent organic framework material, PT-COF, was synthesized using 2,3-dihydroxyterephthalaldehyde and 1,3,5-tri(4-aminophenyl)benzene as reaction monomers; 2) In situ growth of SnIn4S8 on the surface of the PT-COF is carried out by a wet chemical method to obtain the core-shell composite photocatalyst SnIn4S8 / COF.

3. A method for preparing the core-shell composite photocatalyst SnIn4S8 / COF as claimed in claim 2, characterized in that: Step 1) is to add 2,3-dihydroxyterephthalaldehyde and 1,3,5-tri(4-aminophenyl)benzene to acetonitrile, then add acetic acid solution, stir, stand for reaction, centrifuge the reaction solution, wash the obtained solid with N,N-dimethylformamide, tetrahydrofuran and ethanol in sequence, and dry to obtain PT-COF; Step 2) is to disperse the PT-COF prepared in step 1) into anhydrous ethanol, then add SnCl4·5H2O, InCl3·4H2O and thioacetamide, stir, and heat to react. The reaction solution is centrifuged, and the obtained solid is washed with water and ethanol in turn, and dried to obtain the core-shell composite photocatalyst SnIn4S8 / COF.

4. A method for preparing the core-shell composite photocatalyst SnIn4S8 / COF as claimed in claim 3, characterized in that: In step 1), the molar ratio of 2,3-dihydroxyterephthalaldehyde to 1,3,5-tri(4-aminophenyl)benzene is 1:1 to 2:1, and the acetic acid solution is 3 to 12 mol.L -1 ; The stirring is stirring at room temperature for 1 to 10 minutes; the standing reaction is standing at room temperature for 3 days; the washing is washing with N,N-dimethylformamide, tetrahydrofuran and ethanol 1 to 3 times each; the drying is drying at 40-80°C for 12 to 48 hours; In step 2), the dispersion is ultrasonic dispersion; the molar ratio of the added substances is SnCl4·5H2O:InCl3·4H2O:thioacetamide=1:4:8~1:4:16; the stirring is stirring at room temperature for 30~60min; the heating reaction is heating to 60~80℃ for 2~4h; the washing is washing with water and ethanol respectively 1~3 times in sequence; the drying is drying at 40-60℃ for 12~48 hours.

5. Use of the core-shell composite photocatalyst SnIn4S8 / COF as described in any one of claims 1 to 4 in the preparation of hydrogen peroxide, wherein the core-shell composite photocatalyst SnIn4S8 / COF is used as a catalyst in the photocatalytic generation of hydrogen peroxide.

6. The use according to claim 5, characterized in that: The light source used in the photocatalytic reaction of generating hydrogen peroxide is a 300W xenon lamp with a 420nm cut-off filter.